Association of different digital media experiences with paediatric dry eye in China: a population-based study. Issue 11 (30th November 2022) - Ma, Junxin; Zhu, Hui; Guo, Wei; Li, Rui; Shen, Shiya; Wang, Yun; Huang, Dan; Zhang, Xiaohan; Fu, Zhujun; Zhao, Andi; Chen, Danni; Si, Jiahao; et al.
Abstract : Objective: To investigate the ocular surface effects of different digital media experiences in Chinese elementary school students. Design: Population-based cross-sectional study was used. Setting: 14 randomly selected primary schools in Yuhuatai District, Nanjing, China Participants: 2, 694 students between 7 and 8-year-old. Outcome Measures: Prevalence of and risk factors for different types of dry eye disease，and different digital media experience with different ocular signs. Results: The prevalence of 'symptomatic DED' was 8.7% (95% CI 7.6% to 9.8%) and 'definite DED' prevalence rate was 5.5% (95% CI 4.7% to 6.4%). In multivariable logistic regression model, allergic conjunctivitis (OR=4.33, 95% CI (3.01 to 6.23), p<0.001), more than 1 hour per day on outdoor activity (OR=0.69, 95% CI (0.49 to 0.99), p=0.043), smartphone (OR=2.73, 95% CI (1.51 to 4.91), p=0.001), tablet (OR=2.09, 95% CI (1.07 to 4.07), p=0.030) and homework (OR=1.86, 95% CI (1.22 to 2.83), p=0.004) were independently associated with 'definite DED', while allergic conjunctivitis (OR=5.58, 95% CI (4.12 to 7.55), p<0.001), more than 1 hour per day on outdoor activity (OR=0.72, 95% CI (0.53 to 0.97), p=0.028), smartphone (OR=2.60, 95% CI (1.55 to 4.35), p<0.001), tablet (OR=1.84, 95% CI (1.02 to 3.34), p=0.044) and homework (OR=2.57, 95% CI (1.84 to 3.60), p<0.001) were independently associated with 'symptomatic DED'. Conclusions: Using smartphones or tablets for an average of more than 1 hour per day through the course of a year is independently associated with paediatric DED.